Is action potential duration of the intact dog heart related to contractility or stimulus rate? - Drake, Angela J. (1982)
1. The contractility (maximum rate of rise of left ventricular pressure) and action potential duration were measured in intact closed-chest anaesthetized dogs with complete atrioventricular dissociation and β-adrenergic blockade. 2. Measurements were confined to test beats following a 1 sec interval. Prior to the test interval (priming period) a variety of potentiating stimulus trains were introduced. 3. When the frequency of stimulation was increased in the priming period (frequency potentiation), there was an inverse relationship between action potential duration and contractility of the test beat. 4. When the test beat was potentiated by a single beat terminating the priming period with one short interval (post-extrasystolic potentiation), there was no relationship between the action potential duration and contractility of the test beat. 5. Paired pulse stimulation was used for any given frequency to vary contractility by short interval potentiation. For any given frequency of stimulation there was no relationship between action potential duration and contractility of the test beat. For any given value of contractility, action potential duration decreased with increased frequency of stimulation. 6. The introduction of a high frequency train caused a step decrease in action potential duration on the first beat of the train. This was followed by a further slow decline in action potential duration with a time course of over 3 min. These two changes could be dissociated by the introduction during the train of one second interval test pulses, which only showed the slow shortening. 7. The lack of a consistent relationship between action potential duration and contractility of the test beat disagrees with the hypothesis that repolarization is controlled by the activator calcium responsible for the contractility. The action potential shortening associated with increased frequency is related to the frequency change per se. 8. The slow time course of change in action potential duration following an increase in stimulation frequency suggests that these changes are caused by the accumulation of an ion or metabolite, or possibly by changes of activity of the electrogenic Na(+)—K(+) pump.